P027 Re-testing of patients with positive chlamydia results in primary care. (8th June 2017) - McConnell, Sarah; Hutchinson, Jane; Symonds, Merle
Abstract : Introduction: We aimed to establish how many young people (aged 15–24 years) diagnosed with genital Chlamydia infection in General Practice (GP) in 2015 in an inner city area had Partner Notification (PN) discussed with them and were offered repeat testing three-six months after initial diagnosis in line with BASHH guidelines. Methods: We identified young people with positive Chlamydia diagnoses made in GP in 2015 by searching the Chlamydia screening dataset from the hospital laboratory. We cross referenced with subsequent data sets for the year 2015 onwards to see if/when the patient was retested and where they were re-tested. For those re-tested in local GU clinics, we checked their records for evidence of PN initiated in primary care. Results: Preliminary data from January – June 2015 shows that sixty nine 15–24 year olds were diagnosed with Chlamydia in GP; 11 re-tested within six months, seven of these between one and three months post-initial infection of which one was positive. Three of the 11 re-tested in GU clinics; two of these reported PN initiated by GP. Discussion: Results so far show less than 1 in 5 young people diagnosed with Chlamydia in GP are being re-tested appropriately. It is possible that patients are travelling outside the area for re-testing and are missed by our sampling. Recommendations should include routine recall in GP for re-testing after three months to increase re-test rates.